Study on the lithology of stone chimes (stone musical instruments in ancient China) and Lingbi stone. (10th July 2019) - Liuliu, L.; Ying, Q.; Mingyue, Y.; Qiao, H.
Abstract : The oldest extant musical instruments in the world are stone chimes. This music was created by the 'eight tones' that could be produced by these 'stone' voices. Although many of these stone chimes have been unearthed from sites predating the Spring and Autumn Period and the Warring States Period in China, their discussion in archaeological reports is usually not very thorough. In this paper, the ancient and modern samples are analysed from the point of view of lithology. The aim is to explore how the ancients chose to make these stones, and to check that the type of stone from which these ancient Chinese stone chimes are made is actually those recorded in previous studies. The results show that most of the ancient stone chimes in China are made of limestone. These chimes required a material with a single, homogeneous and compact mineral composition. Lingbi chimes (a kind of 'lithophone' produced in Lingbi county, China, are pure in composition and have a fine microcrystalline structure, which is the best choice for making stone chimes. This paper makes a systematic study of the lithology of Chinese stone chimes. The results supplement a significant lacuna in the study of 'lithophone' and ancient stone instruments both in China and on a more global scale.